FACTORS FOR ESTABLISHMENT OF THE COMMITTEE ON RELIGIOUS AFFAIRS UNDER THE CABINET OF MINISTERS OF THE REPUBLIC OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
This article provides information on the factors necessary for the establishment of the Committee on Religious Affairs under the Cabinet of Ministers of the Republic of Uzbekistan.